Unfinished business paintings from the 1970s and 1980s by Ross Bleckner, Eric Fischl and David Salle - Pagel, David 1961-; Pagel, David 1961-; Sultan, Terrie 1952- (Delmonico Books, 2016)
Published to accompany the exhibition of the same name held at Parrish Art Museum, Water Mill, New York, 30 July-16 October, 2016